PENINGKATAN SIKAP ILMIAH SISWA DALAM PEMBELAJARAN BIOLOGI KELAS XI IPA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Yustina ' '; Wan Syafii '; Vina Apriliana ' (Program Studi Pendidikan Biologi, 2014)
There have been studies to determine the application of the learning model ofProblem Based Learning (PBL) to the scientific attitude of students in learningbiology class XI IPA SMAN 4 Pekanbaru Academic Year 2013/2014. This study wasconducted in May 2014 with a sample of students of class XI IPA 1 (grade control) bythe number of students 33 and XI IPA 4 (experimental class) by the number ofstudents 32. The parameters used in the study of critical attitude, honest, open,conscientious and earnest. Collecting data using a scientific attitude observation sheet.Average scientific attitude in the experimental class was 84.39% in both categories,while the control class with 40.69% less category. Based on the research results, it canbe concluded that there are differences between the scientific attitude of studentsusing the experimental class learning model PBL in the learning process incomparison with the control class learning using lecture and discussion.Keywords: Scientific Attitudes, High School Senior, Problem Based Learning (PBL)